Career development within the context of the South African National Qualifications Framework - Keevy, James; LLoyd, Shirley; West, Paul (South African Journal of Higher Education, 2016)
This article presents a descriptive account of the national approach to career development that is being introduced in South Africa through the establishment of the National Qualifications Framework (NQF) and Career Advice Service by the South African Qualifications Authority (SAQA) and the Department of Higher Education and Training. The article attempts to reflect on the approach followed by arguing for the recognition of the underlying career development theory and also by inviting constructive engagement from both the South African and international career development community. By recognising the emerging (also referred to as qualitative) approach to career counselling that is gaining favour in the international context, the article explores the influences on this emerging South African career counselling model. In particular, consideration is given to the important influence on the model through learnings from a career counselling centre established in the 1970s during the apartheid era, similar developments in the United Kingdom and New Zealand, as well as the findings of a comprehensive review of the career counselling landscape commissioned by SAQA in 2009 (Flederman 2009). The unique association of the national approach to career counselling with the South African NQF is put forward as a distinguishing factor with significant potential that needs to be further exploited.